الدفتر العقاري كسند إثبات للملكية العقارية الممسوحة - سعودي, سعيد (جامعة الوادي University of Eloued, 2019)
ملخص: عملت الدولة الجزائرية منذ استرجاع استقلالها على بسط سيادتها على إقليمها، وشكلت عملية التطهير العقاري جزء كبيرا من اهتمامها، بهدف إيجاد آليات قانونية تثبت الملكية العقارية بشكل رسمي، حتى تتمكن الدولة من مراقبة الملكية العقارية من جهة واستغلالها الأمثل تماشيا ومتطلباتها وحاجياتها لبناء تنميتها الصناعية والفلاحية والحضرية من جهة ثانية، لذا عززت وضعها في ذلك من خلال الانتقال من النظام الشهر الشخصي إلى نظام الشهر العيني الذي يقوم على المسح العقاري، والذي من آثاره تسليم الدفتر العقاري، كسند ملكية يعتبر بمثابة بطاقة تعريف العقار وتحديد هويته، وما ينشأ عليه من تغيرات قانونية: كتغير المالك أو تغير طبيعة العقار من فلاحية إلى حضرية أو تغيرات مادية كالبناء والتقسيم والتجزئة، وتطرقـنــــــــــا لهذه الورقـــــــة البحثية فـي مـحوريـــــن: المحور الأول: مفهوم الدفتر العقاري من خلال التطرق لتعريف الدفتر العقاري، وتحديد طبيعته القانونية ونموذجـه. المحور الثاني: تنظيم الدفتر العقاري: من خلال التطرق لكيفية إعداده وتعديله وتسليمه. الكلمات المفتاحية: العقار، الدفتر العقاري، الملكية العقارية، المسح العقاري. Abstract: Since the restoration of its independence, the Algerian state has exercised its sovereignty over its territory. The real estate clearance process has formed a large part of its interest in order to find legal mechanisms that prove real property ownership so that the state can control the real estate property on the one hand and its optimal utilization in accordance with its requirements and needs to build its Industrial, agricultural and urban development, On the other hand, it has strengthened its position by moving from the personal month system to the real estate survey month system, which has the effect of handing over the property book, as a title deed identifying the property and identifying it, The legal changes such as changing the owner or changing the nature of the property from agricultural to urban or material changes such as construction, division and retail, and we addressed this paper in two axes: The first axis: the concept of the book of the real estate by addressing the definition of the book, and determine the legal nature and model. The second axis: Organizing the real estate book: by addressing how to prepare, modify and deliver it. Keywords: real estate, real estate book, real estate property, real estate survey
Keywords: العقار. الدفتر العقاري. الملكية العقارية. المسح العقاري